HIV testing and sero‐prevalence among methamphetamine users seeking substance abuse treatment in Cape Town. (14th December 2015) - Gouse, Hetta; Joska, John A.; Lion, Ryan R.; Watt, Melissa H.; Burnhams, Warren; Carrico, Adam W.; Meade, Christina S.
Abstract: Introduction and Aims: Methamphetamine use is highly prevalent in parts of South Africa, and there is concern this will contribute to the country's substantial HIV epidemic. We examined the feasibility of implementing routine HIV testing at a community‐based substance abuse treatment centre in Cape Town and determined the HIV sero‐prevalence among methamphetamine users seeking treatment at this site. Design and Methods: In this cross‐sectional study, 293 participants completed measures of demographics, substance use and HIV treatment. HIV sero‐prevalence was determined by a rapid finger‐prick HIV test, and prior HIV diagnosis was confirmed via clinic records. Results: The majority of participants were male and self‐identified as 'Coloured', with a mean age of 28 years. The HIV sero‐prevalence was 3.8%. Of the 11 participants who tested HIV positive, four were newly diagnosed. HIV‐positive and HIV‐negative participants were comparable on demographic and substance use factors. Uptake of HIV testing among all clients at the drug treatment centre increased from <5% prior to study initiation to 89% after study completion. Measures implemented to ensure high rates of HIV testing were regarded as sustainable. Discussion and Conclusions: Our study suggests that integrating routine HIV testing into substance abuse treatment is feasible in a community‐based health centre. The low HIV prevalence among this sample of treatment‐seeking methamphetamine users highlights the potential benefits of supporting expanded efforts to optimise HIV prevention with this young adult population. [Gouse H, Joska JA, Lion RR, Watt MH, Burnhams W, Carrico AW, Meade CS. HIV testing and sero‐prevalence among methamphetamine users seeking substance abuse treatment in Cape Town. Drug Alcohol Rev 2016;35:580–583]